SURGICAL CHARACTERISTICS OF STAGE I-IIA NON-SMALL CELL LUNG CANCER (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe surgical characteristics of stage I-IIA non-small cell lungcancer.Subjects and methods: An uncontrolled intervention study on 83 patients diagnosedwith stage I - IIa non-small cell lung cancer who underwent thoracoscopy at MilitaryHospital 175 from January 2015 to December 2020.Results: The average surgical time in the study was 137.5 minutes and the blood losswas not much. Small incisions have an average length of 2.95cm, high aesthetics andlow postoperative pain (5.92 days). The patient had a tumor that pulled the visceralpleura 62/83 (74.7%); 21/83 (25.3%) patients with tumors located in parenchyma;6/83 (7.2%) patients had lung adhesions to the chest wall. There were 2 (2.4%) patientswith bleeding complications that required conversion to open surgery; After surgery,there were 7 complications including 1 (1.2%) pneumonia; 1 (1.2%) empyema causedby green pus bacilli; 5 (6.0%) cases of gas leak lasting more than 7 days.Conclusion: Tumor characteristics in surgery include features of tugging visceralpleura, tumor located in parenchyma, lung sticking to chest wall. Commoncomplications include bleeding. Complications after surgery include pneumonia,empyema caused by green pus bacilli, prolonged gas.
Keywords: Non-small cell lung cancer, surgery.